THE IMPACT OF FINANCIAL AND ADMINISTRATIVE CORRUPTION ON TAX REVENUES FOR FINANCING STATE PUBLIC BUDGET - Lina Khaled Jaafar; Khaldoun Salman Muhammad (Scholars Digest Publishing, 2024)
Financial corruption is the misuse of government employees' positions in all sectors to achieve personal gains. This study searched the impact of financial and administrative corruption (henceforth FAC) on tax revenues to finance the state’s public budget. The study sample consisted of 50 employees of the General Tax Authority. The study adopted the significance value in testing the research hypotheses instead of the tabular value for result accuracy. All indicators (sig) of significance were calculated using SPSS. Results revealed a notable correlation between the influence of FAC and tax revenue. The results also indicated a significant correlation between the effects of FAC and the financing of the state's public budget. The study has shown a substantial impact of FAC on tax revenue and funding for the public budget. Hence, the study results imply a significant correlation among FAC, tax revenue, and public budget funding, underscoring the intertwined influence of FAC on tax revenue and state budget financing.
Keywords: FAC, public budget, tax revenues.